Surgical Management of Midshaft Clavicle Fractures with Locking Plate Fixation: A Prospective clinical study - Surapathi Sankararao (International Journal of Medical and Biomedical Studies, 2026)
Background: Displaced midshaft clavicle fractures are common injuries that may result in malunion, non-union, and functional impairment when treated conservatively. Precontoured locking compression plates (LCPs) provide stable fixation, restoration of clavicular alignment, and facilitate early mobilization. This study evaluated the clinical, radiological, and functional outcomes of surgical fixation of displaced midshaft clavicle fractures using precontoured LCPs. Materials and Methods: A prospective observational study was conducted in 50 adult patients presented with displaced midshaft clavicle fractures and underwent open reduction and internal fixation using precontoured locking plates. Patients were assessed clinically and radiologically during follow-up. Functional outcome was evaluated using the Constant-Murley Score. Time to clinical and radiological union, range of motion, hospital stay, and postoperative complications were recorded. Results: The study included 42 males (84%) and 8 females (16%), with a mean age of 31.16 years. Road traffic accidents were the predominant mechanism of injury (90%), while 10% sustained fractures following falls. Left-sided fractures accounted for 56% and right-sided fractures for 44%. According to the Robinson classification, 4 (8%) fractures were Type 2A2, 32 (64%) were Type 2B1, and 14 (28%) were Type 2B2. The mean operative time was 50.26 ± 11.04 minutes, and the mean hospital stay was 7.9 days. Most patients underwent surgery within 5 days of injury. Full shoulder range of motion was achieved in 42 patients (84%). Radiological union was achieved by 14 weeks in 35 patients (70%), while the remaining 15 patients (30%) achieved union after 14 weeks. The mean time to radiological union was 15.04 ± 1.73 weeks, with no cases of non-union. At 24 weeks, the mean Constant-Murley Score was 96.5 ± 7.2. Functional outcome at 24 weeks was excellent in 41 patients (82%), good in 7 (14%), and fair in 2 (4%). Postoperative complications included superficial infection in 1 patient (2%), plate prominence in 3 (6%), and restriction of shoulder movements in 3 (6%). No implant failure or non-union was observed. Conclusion: Precontoured locking plate fixation of displaced midshaft clavicle fractures resulted in high rates of fracture union, satisfactory shoulder function, and early restoration of range of motion. The procedure was associated with a low rate of major complications and no cases of non-union or implant failure. Precontoured LCP fixation appears to be an effective and reliable surgical option for appropriately selected patients with displaced midshaft clavicle fractures. Keywords: Clavicle fracture; midshaft fracture; locking compression plate; precontoured plate; open reduction and internal fixation; Constant-Murley Score; fracture union